Comparative Analiysis of Financial Performance of Sharia Commercial Bank Before and During The Covid-19 Pandemic - Siti Aliyah; Fatimah Yatimatul Hidayah (EKOBIS SYARIAH, 2022)
This study aims to determine the differences in the financial ratios of sharia commercial bank before the time of the Covid-19 pandemic in terms of liquidity using the FDR ratio, solvency using the CAR ratio and profitability using the ROA ratios for the 2019-2020 period. The data used is secondary data obtained from the bank quarterly financial reports that have been published on the official website of the Financial Services Authority (OJK). This research is a quantitative research. Sampling was carried out by purposive sampling, in order to obtain a sample of 4 sharia commercial banks. The analysis technique used in this study is the Paired Sample T-Test. To determine the normality of the data used the normality test (One-Sample Kolmogorov-Smirnov Test) and the Descriptive Statistical Test. The results of this study indicate that based on the liquidity ratio and profitability ratio at sharia commercial banks before the Covid-19 pandemic with the Covid-19 pandemic, there is a significant difference. Meanwhile, based on the Solvency ratio at Commercial Banks before the Covid-19 pandemic with the Covid-19 pandemic there was no significant difference.